2010
DOI: 10.1111/j.1365-2389.2009.01211.x
|View full text |Cite|
|
Sign up to set email alerts
|

The spatial and temporal organization of soil water at the field scale as described by electrical resistivity measurements

Abstract: Characterizing water processes at the field scale requires an accurate and high-resolution description of the variability of representative state variables, such as water content. Obtaining these data, however, is unrealistic with conventional soil water sensors; we therefore propose an empirical approach to measure water content based on electrical resistivity. This geophysical method provides exhaustive and time-repetitive information on the resistivity of a DC signal. Resistivity can be used to estimate wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 48 publications
4
37
1
3
Order By: Relevance
“…Desse modo, por possuir natureza não invasiva, de baixo custo e fornecer medidas sensíveis às características do meio, o método elétrico de corrente contínua permite diagnosticar, de maneira indireta, variações de umidade do solo e do nível do lençol freático (Besson et al 2010). A resistividade é inversamente proporcional ao volume de água presente no solo ou rocha e ao conteúdo de material em solução na água (Orellana, 1972).…”
Section: -Introduçãounclassified
“…Desse modo, por possuir natureza não invasiva, de baixo custo e fornecer medidas sensíveis às características do meio, o método elétrico de corrente contínua permite diagnosticar, de maneira indireta, variações de umidade do solo e do nível do lençol freático (Besson et al 2010). A resistividade é inversamente proporcional ao volume de água presente no solo ou rocha e ao conteúdo de material em solução na água (Orellana, 1972).…”
Section: -Introduçãounclassified
“…Studies conducted by Besson et al (2010) observed that spatial and temporal variability in soil electrical resistivity has a strong relationship with the spatial and temporal variability in soil water content. According to these authors, the sites with greater water content have lower electrical resistivity and vice versa.…”
Section: Correlation Of Eca With Soil Attributesmentioning
confidence: 99%
“…Table 4.10 lists applications of methods not mentioned in the previous tables. The application of MultiContinous Electrical Profiling (MuCEP) in predicting soil moisture content might be interesting (Cousin et al, 2009;Besson et al, 2010). These studies did not include validation experiments, however.…”
Section: Ground Penetrating Radarmentioning
confidence: 99%